Genetic relationships among Eriobotrya species revealed by genome‐wide RAD sequence data. Issue 8 (21st March 2017) - Yang, Xianghui; Najafabadi, Samaneh Kazemiani; Shahid, Muhammad Qasim; Zhang, Zhike; Jing, Yi; Wei, Weiling; Wu, Jingcheng; Gao, Yongshun; Lin, Shunquan
Abstract: Restriction site‐associated DNA sequencing (RAD‐seq) was used to illuminate the genetic relationships among Eriobotrya species. The raw data were filtered, and 221 million clean reads were used for further analysis. A total of 1, 983, 332 SNPs were obtained from 23 Eriobotrya species and two relative genera. We obtained similar results by neighbor‐joining and maximum likelihood phylogenetic trees. All Eriobotrya plants grouped together into a big clade, and two out‐groups clustered together into a single or separate clade. Chinese and Vietnam accessions were distributed throughout the dendrogram. There was nonsignificant correlation between genotype and geographical distance. However, clustering results were correlated with leaf size to some extent. The Eriobotrya species could be divided into following three groups based on leaf size and phylogenetic analysis: group A and group B comprised of small leaves with <10 cm length except E. stipularis (16.76 cm), and group C can be further divided into two subgroups, which contained medium‐size leaves with a leaf length ranged from 10 to 20 cm and a leaf length bigger than 20 cm. Abstract : We obtained similar results by both Neighbor‐joining and maximum likelihood phylogenetic trees. All Eriobotrya plants grouped together into a big cluster, and two out‐groups clustered together into a single or separate cluster. Chinese and Vietnam accessions were distributed throughout the dendrogram.